Catellatospora sichuanensis sp. nov., a novel actinobacterium isolated from soil. Issue 5 (29th April 2020) - Liu, Chaolan; Guo, Yidong; Li, Li; Wang, Xiwei; Lin, Jiafu; Wang, Xinrong; Li, Jianghua; Chu, Yiwen
Abstract : A novel actinobacterium, designated strain H14505 T, was isolated from a soil sample collected in Hong Yuan, Sichuan, southwest PR China. The temperature, pH and NaCl ranges for growth were determined to be 15–35 °C (optimum, 28 °C), 6.0–8.0 (optimum, pH 7.0) and 0–2 % (w/v; optimum without NaCl), respectively. The polar lipdis detected for strain H14505 T were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, glycolipid and four unidentified lipids. The predominant menaquinones of strain H14505 T were MK-9(H4 ) and MK-9(H6 ), and the prevalent fatty acids (>10 %) were C18 : 1  ω9 c, C17 : 1  ω8 c, summed feature 5 (anteiso-C18 : 0 / C18 : 2  ω6, 9 c ) and C16 : 0 . Phylogenetic analysis based on 16S rRNA gene and whole-genome sequences indicated that strain H14505 T showed high similarity to Catellatospora vulcania NEAU-JM1 T (99.0 %) and Catellatospora paridis NEAU-CL2 T (99.0 %), and formed a monophyletic clade within the the genus Catellatospora in the phylogenetic trees. However, the average nucleotide indentity and DNA–DNA hybridization values between strain H14505 T and closely related Catellatospora species showed that it belonged to a distinct species. Furthermore, the results of morphological, physiological and biochemical tests allowed further phenotypic differentiation of strain H14505 T from its closest relatives. Thus, it is proposed that strain H14505 T represents a novel species of the genus Catellatospora, for which the name Catellatospora sichuanensis sp. nov. is proposed. The type strain of Catellatospora sichuanensis is H14505 T (=JCM 32394 T =CICC 11042 T ).